Serum progesterone and estradiol levels in Jafarabadi buffaloes - DUGWEKAR, Y G; SARVAIYA, N P; PATEL, M D; TAJNE, K R; SHAH, R R (The Indian Journal of Animal Reproduction, 2023)
The present study reports circulating serum progesterone (P 4) and estradiole- I 7~ (E2) levels duringdifferent phase of reproduction, viz, puberty, oestrous cycle, pregnancy, parturition and post-partum period inJafarabadi buffaloes. The level of P 4 and E2 in pre-pubertal (n=7) Jafarabadi buffaloes were in the range of 0.07 ± 0.02to 1.90 ±0.57 ng/ml and 24.85 ± 11.80 to 76.0 ±. 4.88 pg/ml respectively. At estrus (n=6), the basal level of P4 was 0.55± 0.22 ng/ml, increased to 2.90 ± 0.46 ng/ml during diestrus and remained elevated ( 3.23 ± 0.16 ng/ml) in conceivedanimal during first trimester of gestation. The peak E2 at estrus (n=6) was 40.20 ± 19.68 pg/ml, which fell belowI 0.00 pg/ml for rest of the estrus cycle. The E2 concentration also remained elevated through out the gestation periodand reached at peak of 129.33 ± 33.3'8 pg/ml towards parturition. During purperium (n=IO), up to three months theserum P4 and E2 levels remained at a basal level indicating very little ovarian activity. In some animals post partumonset of estrus was delayed up to ten months. These animals had only basal levels of P4 and E2 and complete inactiveovaries. from this study, it can be concluded that the values with respect to serum P4 and E2 levels at different phasesof reproduction in Jafarabadi buffaloes are similar to the values rep~rted for other breeds of buffaloes.
Keywords: Progesterone; Estradiol; Jafarabadi buffalo; Reproduction